Grounding of veterinary prevention and permanent prevention on rabbit farms - Сачук, Р. М.; Демчук, М. В. (Scientific Progress & Innovations, 2012)
Based on the literature review and personal research on methods for assessing the impact of confounding factors on the rabbits health the plan of general veterinary prevention (GVP) of rabbit farms for developing specific veterinary technology of rabbit breeding products has been offered. The plan includes significant new demands as progressive technology, welfare of rabbits maintenance systems, balanced nutrition with valuablel feed, grounds of species selection and breeding work with herd. Based on the proposed plan GVP started correction of breedingg technology, maintenance and breeding rabbits in Ukraine in «Ecokrol» Volochynsky district, Khmelnytsky region.